Volume 1: Turbomachinery 1994
DOI: 10.1115/94-gt-334
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Prediction of Blade-Passing Frequency Noise Generated by a Centrifugal Blower

Abstract: The blade-passing frequency noise, abbreviated to BPF noise, of low specific speed centrifugal blower is analyzed by separating the frequency-response of the transmission passage and the intensity of the noise source. Frequency-response has previously been evaluated by the authors using a one-dimensional linear wave model, and the results have agreed well with the experimental response in a practical range of the blower speed. In the present study, the intensity of the noise source is estimated by introducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…It mainly possesses a great deal of outstanding advantages, for instance high pressure coefficient, small size coefficient, and low noise. 1,2 In general, the performance of centrifugal fans has drawn widespread concern. It is of great significance to improve the performance of centrifugal fans, which can not only achieve the purpose of energy conservation, but also benefit the development of the fan industry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It mainly possesses a great deal of outstanding advantages, for instance high pressure coefficient, small size coefficient, and low noise. 1,2 In general, the performance of centrifugal fans has drawn widespread concern. It is of great significance to improve the performance of centrifugal fans, which can not only achieve the purpose of energy conservation, but also benefit the development of the fan industry.…”
Section: Introductionmentioning
confidence: 99%
“…Forward curved centrifugal fans are compact and quiet, but classically have low efficiency and are consequently at risk of being regulated out of the market. 2,3 Lin and Wu 3 performed an extensive experiment to study the influences caused by the deep contour inlet section and the central body for a forward curved centrifugal fan. Their work showed that the central body does enhance the static efficiency by 10%, whereas the deep inlet section results in a negative effect on the fan performance.…”
Section: Introductionmentioning
confidence: 99%
“…Since the noise, which is called an interaction tone noise (ITN), is considered to be caused by direct impingement of the impeller-discharged flow on the diffuser vane, the leading edge geometries of the diffuser vane play an important role in discussing the noise generation mechanisms. Although the interaction between impeller-discharged flow and diffuser vanes is an obvious and powerful noise source, surprisingly little research has been reported on the ITN [1][2][3][4][5]. Furthermore, the frequency of the ITN coincides with that of the blade-passing frequency components, abbreviated to BPF components, so the noise could dominate the overall noise level if sufficient care is not taken.…”
Section: Introductionmentioning
confidence: 95%
“…Many authors have studied the noise generated by centrifugal fans and they have shown that the main source of aerodynamic tonal noise generation is the interaction between the non-uniform impeller flow and the fixed volute tongue [3,4]. According to these investigations, the location of the effective noise source is restricted to the vicinity of the volute tongue, and the extension of the effective source region could be determined by a correlation analysis between the acoustic pressure radiated by the fan and the pressure fluctuation on the volute surface.…”
Section: Introductionmentioning
confidence: 99%